Inclusionary regimes, party institutionalization and redistribution under authoritarianism. Issue 7 (2nd October 2020) - Pelke, Lars
ABSTRACT: This article examines the variation in income redistribution across autocracies. It argues that the degree of electoral uncertainty affects two mechanisms that shape the redistributive nature of autocratic regimes. The inclusion and exclusion from political power on the grounds of socioeconomic and social attributes, and the institutionalization of political parties determine the incentive and capacity for autocrats to redistribute income and economic benefits. Using data from 105 autocracies between 1960 and 2016 and within-between random effects models, I estimate within- and between-country effects of the variables. The analysis suggests that more inclusionary ruling coalitions have higher levels of income redistribution compared to more exclusionary regimes. Second, regimes with higher levels of party institutionalization redistribute more than regimes in which authoritarian parties are less institutionalized. Third, the effects are largely conditional on the electoral uncertainty. This analysis improves our understanding about how authoritarian regime characteristics affect the political economy of those regimes. Its findings provide empirical support for the selectorate theory and the literature on authoritarian institutionalization and have implications for democratization and democratic consolidation.